2006
DOI: 10.1007/s11270-006-9168-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxalate and Humic Acid on Arsenate Sorption by and Desorption from a Chinese Red Soil

Abstract: Abstract. Studies on arsenate (As(V)) sorption and desorption have been mainly limited to soil minerals and sorption and desorption reactions in whole soils are poorly understood. In this study the sorption of As(V) by and phosphate-induced desorption from a Chinese red soil were studied in the presence of oxalate and humic acid (HA). Arsenate was strongly sorbed mainly through ligand exchange reactions on the soil. Arsenate sorption decreased in the presence of oxalate or HA. Oxalate and HA influenced As(V) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…[19, 20] Studies suggest that dissolution of Al and Fe species by organic acids leads to As release or that there is competitive sorption between organic acids and As (or a combination of the two processes play a role). [8, 2123] Oxalic acid is often included in sequential soil extraction schemes investigating As phases. [2427] Additionally, studies have shown As release in the presence of oxalic acid [7, 8, 22, 28, 29] and inhibition of As sorption in the presence of oxalic acid under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[19, 20] Studies suggest that dissolution of Al and Fe species by organic acids leads to As release or that there is competitive sorption between organic acids and As (or a combination of the two processes play a role). [8, 2123] Oxalic acid is often included in sequential soil extraction schemes investigating As phases. [2427] Additionally, studies have shown As release in the presence of oxalic acid [7, 8, 22, 28, 29] and inhibition of As sorption in the presence of oxalic acid under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some other researchers also reported that HA, oxalate and salicylic acid could form soluble complexes with Fe and Al to dissolve clay minerals and adsorption was reduced accordingly [41,42].…”
Section: Effect Of Humic Acidmentioning
confidence: 99%
“…Further, previous studies [10,20,21,22] have also reported the higher adsorption affinity of HA molecules for iron oxide than As species, which tends to change the surface properties of sorbent and compete with As species for active sorption sites, in turn increasing the mobility of As in water. The presence of HA also impedes the precipitation of ferric hydroxide at lower coagulant dosage due to the formation of soluble complexes with Fe 3+ during the C/F/S process [23,24,25]. A recent study [17] exploring the complexation behavior of As with HA and FA in water found results indicating the increased binding affinity of organic ligands with As(V) as compared to with As(III).…”
Section: Introductionmentioning
confidence: 99%